PENGEMBANGAN METODA MINIMUM RADIAL SEPARATION UNTUK EVALUASI GEOMETRI KESILINDRISAN - Rizky, Yosha
Abstract: This research proposes a method for evaluating cylindricity using Minimum Radial Separation (MRS). A set of coordinate points of a cylinder is acquired through slicing technique. Slicing technique is intended to reduce the difficulty of calculating orthogonal distance of a complex work piece. Hodgson (1999) stated that for evaluating cylindricity requires minimum combinations of 6 points in order to evaluate the minimum zone of a cylinder. Considering the slicing plane of a cylinder as a circle, combination of points for minimum zone can be reduced to 4 points. Slicing a cylinder perpendicular to the axis of cylinder intends to evaluate cylinder's roundness. MRS method calculates minimum zone of a cylinder by minimizing the radial distance differences of Largest Inscribed Circle (LIC) and Smallest Circumscribed Circle (SCC). LIC and SCC is achieved by constructing Nearest Point Voronoi Diagram (NPVD), Farthest Point Voronoi Diagram (FPVD) and intersection of NPVD-FPVD. The smallest among the three is selected to determine MRS for evaluating cylindricity. Center points of MRS's circle at all slicing plane is calculated using MRS method to evaluate the straightness of axis. Minimum Radial Separation development by utilizing slicing technique and Voronoi diagram evaluates cylindricity by combining roundness and straightness of axis. By using this method, variation of cylinder which near the true minimum zone could be achieved and be visualized.